Quadratic buck–boost converter with positive output voltage and continuous input current for PEMFC systems. (21st December 2017) - Rosas-Caro, Julio C.; Sanchez, Victor M.; Valdez-Resendiz, Jesus E.; Mayo-Maldonado, Jonathan C.; Beltran-Carbajal, Francisco; Valderrabano-Gonzalez, Antonio
Abstract: Electrical power processing is an essential component of proton exchange membrane fuel cell (PEMFC or simply FC) conversion systems. The first stage of power conditioning usually consists of a DC–DC converter that enables a suitable DC bus voltage for a load feeder- or grid-tie- inverter. Motivated by the current needs in power conditioning of PEMFC systems, we propose a new power electronics converter. The proposed topology has a quadratic buck–boost voltage gain which allows a wide range of input voltages, providing a fixed output voltage with additional compelling features such as the circumvention of the use of transformers, coupled inductors or extreme duty cycles. Moreover, the input current of the proposed converter is continuous and its output voltage is positive with respect to the input one, which is in sharp contrast with respect to other buck–boost topologies whose output voltages are in general negative. The main principles, steady-state analysis, and a small-signal model for the proposed circuit operating in continuous conduction mode (CCM) are presented in detail. Simulation and experimental results are provided to validate the theoretical analysis. Highlights: A quadratic buck–boost converter is proposed to be used with PEMFC systems. The output voltage is positive and the voltage gain is quadratic. The input current is continuous, highly desirable in fuel cell applications. A design procedure, steady state analysis, and small signal model is provided. Experimental results are provided to validate the principle of the proposition.